Social Investing as Tool to Improve the Quality of Life. Implications for the Sustainable Development and Environmental Vulnerability - KAMENOVA, Mazken; ZHANTELEUOVA, Gulden; MAIDANKYZY, Bayan; LESBAYEVA, Gulnara; AMIROVA, Maral; SHULENBAYEVA, Faya (Journal of Environmental Management and Tourism, 2023)
In recent years, social investment has become a tool for solving economic problems, improving the level and quality of life of the population, increasing life expectancy, leading to conditions for creating new environmentally friendly jobs, expanding the availability of social services, medicine and education, as well as a mechanism for redistributing temporarily free funds between business entities. Active implementation of the social investment mechanism based on the experience of developed countries in the direction of the efficient use of financial resources will lead to the growth of sustainable socio-economic development of Kazakhstan. In the course of the analysis, the authors found that a decrease in the population's monetary income, that is, the level of well-being, a characteristic increase in consumer spending, a decrease in purchasing power, as well as a propensity to save money, require the speedy introduction of social investment mechanisms in order to improve the quality of life of the population of the regions of Kazakhstan to prevent possible social threats. Social investment for the sustainable development of the economy involves the effective interaction of subjects in the process of providing financial resources in order to solve social problems and obtain material benefits for investors.